Hydropower Policy and Site-Level Contestation under the Political Transition: Challenges for Ending the Power Cut in Nepal - Dhungana, Hari; Maskey, Gyanu (Journal of Forest and Natural Resource Management, 2019)
The growing optimism for hydropower development in Nepal over the past few years faces significant bottlenecks amid the country’s political transition. The government’s policies to attract more and more investment in new hydropower projects face the challenge of retaining investors and bringing projects to success, as considerable confusion and uncertainty exist around environmental and social-political demands on the projects. Ongoing political transition retains and harbours greater grey area for local and indigenous rights, labor issues, grievance handling, site-level decision-making, and responding to the widespread resort to obstructionism, blockages, and strikes. This paper draws on the evidence and insights from the case study of hydropower project in Western Nepal and a series of meetings in Kathmandu with water sector stakeholders to identify key challenges for the development and implementation of hydropower projects in terms of physical and social impacts. To achieve policy goals on hydropower development, it is essential to have policy-legal clarity on the above issues in a manner that is understood and legitimated by local stakeholders, and internalized into decision-system at the local level. These conditions will be rendered feasible only with the end of ongoing political transition in favour of a stable, transparent and democratic polity in the country.